ANALISIS YURIDIS PENJATUHAN PIDANA DENDA DI BAWAH KETENTUAN MINIMUM KHUSUS OLEH HAKIM DALAM PERKARA TINDAK PIDANA KORUPSI (STUDI PUTUSAN PENGADILAN TINGGI MEDAN NOMOR 12/PID.SUS-TPK/2017/PT.MDN) - Maria Eleonora Novena Pritasari; Hery Firmansyah (Jurnal Hukum Adigama, 2020)
Corruption is a criminal act that requires extraordinary prevention and handling. One of the efforts to eradicate corruption is the application of special minimum criminal provisions.The implementation of this special minimum criminal sanction needs to be supported by the judge as the law enforcer who determines the severity of the crimes imposed in the judicial system. Often corruption court decisions apply criminal sanctions under a special minimum sentence. Pancasila Sibarani based on Medan High Court Decision Number 12/PID.SUS-TPK/2017/PT.Mdn, was sentenced to a fine of IDR 50,000,000, which deviates from the specific minimum provisions in the law. The research method used in this study is a normative research method based on literature study materials and interviews with practitioners and academics. The results of this study indicate that conviction by judges is entirely dependent on the process of proving and seeking material truth in the case itself. The judge's authority in imposing a sentence must be based on considerations obtained from extracting facts in the trial process.